2006
DOI: 10.1029/2005gl025579
|View full text |Cite
|
Sign up to set email alerts
|

Climate model fidelity and projections of climate change

Abstract: [1] Relative entropy, which is a measure of the difference between two probability distributions, has been calculated for the simulations of the climate of the 20th century from 13 climate models and the observed surface air temperature during the past 100 years. This quantity is used as a measure of model fidelity: a small value of relative entropy indicates that a given model's distribution is close to the observed. It is found that there is an inverse relationship between relative entropy and the sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 10 publications
(10 reference statements)
1
64
0
Order By: Relevance
“…Reliable assessments of these contributing factors depend critically on reliable estimations of natural climate variability, either from the observational record or from coupled climate model simulations without anthropogenic forcings. Several recent studies suggest that the observed SST variability may be misrepresented in the coupled models used in preparing the IPCC's Fourth Assessment Report, with substantial errors on interannual and decadal scales (e.g., Shukla et al 2006, DelSole, 2006Newman 2007;Newman et al 2008). There is a hint of an underestimation of simulated decadal SST variability even in the published IPCC Report (Hegerl et al 2007, FAQ9.2 Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Reliable assessments of these contributing factors depend critically on reliable estimations of natural climate variability, either from the observational record or from coupled climate model simulations without anthropogenic forcings. Several recent studies suggest that the observed SST variability may be misrepresented in the coupled models used in preparing the IPCC's Fourth Assessment Report, with substantial errors on interannual and decadal scales (e.g., Shukla et al 2006, DelSole, 2006Newman 2007;Newman et al 2008). There is a hint of an underestimation of simulated decadal SST variability even in the published IPCC Report (Hegerl et al 2007, FAQ9.2 Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In general, this relation is negative as found for other skill metrics (e.g. by Shukla et al, 2006), however in most cases small and not significant if the models with the worst IAV representation (mainly the models 'g', 'i', 'j' and 'h'; see above) are omitted. One exception is the extratropical summer where a significant negative relation (r ∼ −0.5) between the model's ability to represent extratropical IAV and extratropical temperature change is found.…”
Section: Discussionmentioning
confidence: 65%
“…Some studies (e.g. Shukla et al, 2006) found relations between model fidelity and temperature changes in the future with the 'better' models indicating significantly larger temperature changes in climate projections at least on the global scale.…”
Section: Relations Between Iav Representation and Temperature Projectmentioning
confidence: 99%
“…The problem of global warming projection was considered from the current perspective by [87]. They used the divergence between the equilibrium distribution of various models and the present observed climate/equilibrium distribution as a measure of the veracity of a particular model.…”
Section: Other Recent Applicationsmentioning
confidence: 99%